‘Sort of human’? The divinity and humanity of Homer’s Helen - Blankenborg, Ronald (2022)
In this contribution, I will argue that Homer’s Helen is not a human-nonhuman hybrid, though in the Iliad and the Odyssey, the poet seems reluctant to choose between her divine origin on the one hand, and her human appearance and demeanour on the other. Helen surfaces in literature as a daughter of Zeus, sister of semi-divine twins, and wife and mother to mortals. Allegedly, she caused the Trojan War. In her performance and her speeches, she shows herself as the center of attention, a claim that is never disputed. As she acts and speaks, Helen is on a par with the gods, but without serious regard for mortals. I will argue that the poet’s inability to clearly distinguish between the various personae betrays his implicit predilection for Helen as a goddess in disguise, rather than a supernatural human being. Later tradition and reception acknowledges Helen’s working as a divinity.